Investigation of BTLA tagging variants with risk of esophagogastric junction adenocarcinoma. Issue 12 (13th December 2019) - Tang, Weifeng; Chen, Shuchen; Kang, Mingqiang; Liu, Jun; Liu, Chao
Abstract: Background: Variants in B- and T-lymphocyte attenuator ( BTLA ) gene are likely to affect the function of BTLA protein. Methods: In the present case–control study, we selected BTLA tagging single-nucleotide polymorphisms (SNPs) (rs16859629 T>C, rs1982809 G>A, rs2171513 G>A and rs3112270 A>G) and conducted a case–control study to identify the association of BTLA SNPs with risk of esophagogastric junction adenocarcinoma (EGJA). The present study involved 1236 new incident EGJA cases and 1540 cancer-free controls. Results: The genotypes of BTLA SNPs were analyzed using a SNPscan Kit. No association was also found between the BTLA SNPs and the susceptibility of EGJA in overall comparsion. In subgroup analyses, the BTLA rs1982809 was found to be associated with an increased susceptibility of EGJA (AA versus GG: OR adjusted = 2.09, 95% CI 1.08–4.07, P = 0.030; and AA versus GA/GG: OR adjusted = 1.99, 95% CI 1.04–3.82, P = 0.039). In haplotype comparison, we identified that TAAG haplotype with the order of BTLA rs16859629, rs1982809, rs2171513 and rs3112270 SNPs might increase the susceptibility of EGJA (OR = 3.07, 95% CI = 1.41–6.71; P = 0.003). Conclusion: To conclude, the present study suggests that BTLA Trs16859629 Ars1982809 Ars2171513 Grs3112270 haplotype may increase the susceptibility of EGJA. More studies should be conducted to evaluate whether BTLA polymorphisms may influence the susceptibility of cancer in the future.